The influence of the discovery learning model on students' mathematical representation ability - Rifdayani, Rizkia Huda; Rini Asnawati; Santy Setiawati (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
This study aims to determine the effect of the discovery learning model on students' mathematical representation abilities. The population in this study consists of all eighth-grade students at UPT SMP Negeri 1 Gading Rejo during the odd semester of the 2024/2025 academic year. The sample was selected using the cluster random sampling technique, resulting in 30 students from class VIII-A as the experimental group and 29 students from class VIII-D as the control group. This research is a quasi-experimental study using a pretest-posttest control group design. Data were collected through a mathematical representation ability test. The data analysis technique employed in this study was the t-test. The results indicate that the improvement in students' mathematical representation abilities in the discovery learning model is greater than that of students who received conventional instruction. Thus, it can be concluded that the discovery learning model influences students' mathematical representation abilities.